2007
DOI: 10.1007/s11605-007-0084-4
|View full text |Cite
|
Sign up to set email alerts
|

A 30-Year Analysis of Colorectal Adenocarcinoma in Transplant Recipients and Proposal for Altered Screening

Abstract: The incidence of and 5-year survival after diagnosis of colorectal adenocarcinoma in transplant recipients is markedly different than the general population. Patients are often diagnosed at a younger age. With current screening guidelines, over 25% of at-risk patients would not be screened. We propose modifying these guidelines to allow earlier detection of colorectal cancer in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
72
1
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(81 citation statements)
references
References 29 publications
(49 reference statements)
6
72
1
2
Order By: Relevance
“…By hand searching, another 20 articles were identified. When the exclusion criteria were applied, the final 29 studies were included for review ( Figure 1) (2,6,16,36,37,40) were of high, 15 of medium (3,35,(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)) and 8 of low quality according to the DQS (38,39,(54)(55)(56)(57)(58)(59). A pretransplantation screening protocol for LTx evaluation was mentioned in 2 studies (16,37 (3,6,37,40,45,52,53).…”
Section: Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…By hand searching, another 20 articles were identified. When the exclusion criteria were applied, the final 29 studies were included for review ( Figure 1) (2,6,16,36,37,40) were of high, 15 of medium (3,35,(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)) and 8 of low quality according to the DQS (38,39,(54)(55)(56)(57)(58)(59). A pretransplantation screening protocol for LTx evaluation was mentioned in 2 studies (16,37 (3,6,37,40,45,52,53).…”
Section: Study Selectionmentioning
confidence: 99%
“…After pooling the 10 studies (Figure 4) (2,6,16,37,40,45,49,52,53) (48,65,66 (6,37). One of these two studies reported a mean age of LTx of 56 years (37).…”
Section: Risk Of Crc In Post-ltx Patients: a Meta-analysis Of Follow-mentioning
confidence: 99%
“…Although some studies have identified an increased risk of colorectal neoplasia among these patients (3)(4)(5)(6), the topic remains controversial. (13)(14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…CMV nucleic acids and proteins specifically localized to neoplastic cells in human colorectal polyps and adenocarcinomas have been reported (18). Exclusion criteria were as follows: (1) unwillingness to participate (N = 398), (2) (4) intolerance of cleansing solution intake for colon preparation (N = 25), (5) history of colorectal neoplasia (N = 5) and (6) The results of logistic regression analysis adjusted for age and gender are shown in Table 4.…”
Section: Introductionmentioning
confidence: 99%
“…However, the age still tended to be less than that in CRC in the general population, since one-year CRC prevalence showed a peak in 65 -74 years of males and in over 75 years of females in Japan (33). Another report has demonstrated that transplant recipients under the age of 50 have a 10-fold greater risk of developing CRC (34). On the basis of this result, it has been …”
Section: Discussionmentioning
confidence: 98%